Answer:
Hypotenuse = 6
Step-by-step explanation:
Find attached diagram used in solving the question.
The triangle is a 45°-45°-90° triangle meaning it's two legs are equal. The opposite = adjacent
Since we are told to find hypotenuse, it means the length given = opposite = adjacent = 3√2
Hypotenuse ² = opposite ² + adjacent ²
Hypotenuse ² = (3√2)² + (3√2)²
Hypotenuse ² = 9(2)+9(2) = 18+18
Hypotenuse ² = 36
Hypotenuse = √36
Hypotenuse = 6
Answer:
Because 20 has to be doubled to become 40. While 40 is twice as much as 20 so you just divide 40 by 20 to get 50%.
Explanation:
20 x 20 = 40 = 100%
40 / 20 = 50%
Answer:
The period is 360° ( in radians, the period is 2π)
Step-by-step explanation:
For a sine/cosine (sinusoidal) function in the form
y = ASin(Bx-C) + D, we can say
A is the amplitude
360/B is the period
C is the phase shift
D is the vertical translation
<em>The function given is y = 2Sinx</em>
To find the period, we need 360/B. Since "B" is just "1", the period is
360/1 = 360
Answer:
10.95 (if you need to round 11)
Step-by-step explanation:
:p
Answer:
![\large \boxed{\sf \ \ \ (x+2)(x-\dfrac{1}{2}) \ \ \ }](https://tex.z-dn.net/?f=%5Clarge%20%5Cboxed%7B%5Csf%20%5C%20%5C%20%5C%20%28x%2B2%29%28x-%5Cdfrac%7B1%7D%7B2%7D%29%20%5C%20%5C%20%5C%20%7D)
Step-by-step explanation:
Hello,
let's solve
![x^2+\dfrac{3}{2}x-1=0\\\\ 2x^2+3x-2=0 \ \text{multiply by 2}\\\\\\](https://tex.z-dn.net/?f=x%5E2%2B%5Cdfrac%7B3%7D%7B2%7Dx-1%3D0%5C%5C%5C%5C%3C%3D%3E%202x%5E2%2B3x-2%3D0%20%5C%20%5Ctext%7Bmultiply%20by%202%7D%5C%5C%5C%5C%5C%5C)
![\Delta=b^2-4ac=9+4*2*2=9+16=25](https://tex.z-dn.net/?f=%5CDelta%3Db%5E2-4ac%3D9%2B4%2A2%2A2%3D9%2B16%3D25)
There are two solutions
![x_1=\dfrac{-3-\sqrt{25}}{4}\\\\x_1=\dfrac{-3-5}{4}\\\\x_1=\dfrac{-8}{4}\\\\\boxed{x_1=-2}](https://tex.z-dn.net/?f=x_1%3D%5Cdfrac%7B-3-%5Csqrt%7B25%7D%7D%7B4%7D%5C%5C%5C%5Cx_1%3D%5Cdfrac%7B-3-5%7D%7B4%7D%5C%5C%5C%5Cx_1%3D%5Cdfrac%7B-8%7D%7B4%7D%5C%5C%5C%5C%5Cboxed%7Bx_1%3D-2%7D)
And
![x_2=\dfrac{-3+\sqrt{25}}{4}\\\\x_2=\dfrac{-3+5}{4}\\\\x_2=\dfrac{2}{4}\\\\\boxed{x_2=\dfrac{1}{2}}](https://tex.z-dn.net/?f=x_2%3D%5Cdfrac%7B-3%2B%5Csqrt%7B25%7D%7D%7B4%7D%5C%5C%5C%5Cx_2%3D%5Cdfrac%7B-3%2B5%7D%7B4%7D%5C%5C%5C%5Cx_2%3D%5Cdfrac%7B2%7D%7B4%7D%5C%5C%5C%5C%5Cboxed%7Bx_2%3D%5Cdfrac%7B1%7D%7B2%7D%7D)
So we can write
![x^2+\dfrac{3}{2}x-1\\\\=(x-x_1)(x-x_2)\\\\=(x+2)(x-\dfrac{1}{2})](https://tex.z-dn.net/?f=x%5E2%2B%5Cdfrac%7B3%7D%7B2%7Dx-1%5C%5C%5C%5C%3D%28x-x_1%29%28x-x_2%29%5C%5C%5C%5C%3D%28x%2B2%29%28x-%5Cdfrac%7B1%7D%7B2%7D%29)
Hope this helps.
Do not hesitate if you need further explanation.
Thank you